Drug-drug interactions in intensive care units and potential clinical consequences of these interactions (Annals of Medical Research, 2021)
Aim: Drug-drug interactions (DDIs) are an important factor that can lead to serious health problems by increasing or decreasing the effects of drugs. This study aimed to evaluate the frequency of DDIs in the intensive care unit (ICU).Material and Methods: All patients who were hospitalized for more than 24 h in the ICU of our hospital between January and September 2018 and received 2 or more medications were included in this retrospective study. Frequency and severity of the DDIs were detected using the Rx Mediapharma and Lexi-Interact programs.Results: Of the 972 patients enrolled in the study, 2742 incidences of DDIs were detected in 626 patients (64%). Of the different drug pairs administered, 422 had DDIs, and 64 of those had 10 or more DDIs, constituting 67% of all of the DDIs. The most common potential clinical consequences of DDIs were increased risk of bleeding (12.3%), hyperkalemia (8.2%), arrhythmia (7.9%), and CNS depression (6.6%). Conclusion: The results indicated that DDIs in the ICU were very common in our hospital. Moreover, these results indicated that patients should be closely monitored for the prevention of adverse effects, such as electrolyte disturbance, bleeding risk, and arrhythmia of drugs.
Keywords: Drug-drug interaction; intensive care unit; adverse drug reaction.